Capillary electrophoresis-based immunoassay and aptamer assay: A review - Nevídalová, Hana; Michalcová, Lenka; Glatz, Zdeněk (Electrophoresis, 2020)
Over the last two decades, the group of techniques called affinity probe CE has been widely used for the detection and the determination of several types of biomolecules with high sensitivity. These techniques combine the low sample consumption and high separation power of CE with the selectivity of the probe to the target molecule. The assays can be defined according to the type of probe used: CE immunoassays, with an antibody as the probe, or aptamer-based CE, with an aptamer as the probe. Immunoassays are generally divided into homogeneous and heterogeneous groups, and homogeneous variant can be further performed in competitive or noncompetitive formats. Interacting partners are free in solution at homogeneous assay, as opposed to heterogeneous analyses, where one of them is immobilized onto a solid support. Highly sensitive fluorescence, chemiluminescence or electrochemical detections were typically used in this type of study. The use of the aptamers as probes has several advantages over antibodies such as shorter generation time, higher thermal stability, lower price, and lower variability. The aptamer-based CE technique was in practice utilized for the determination of proteins in biological fluids and environmentally or clinically important small molecules. Both techniques were also transferred to microchip. This review is focused on theoretical principles of these techniques and a summary of their applications in research.
Keywords: Immunoassay; Lab-On-A-Chip Devices; Humans; lidé; aptamery nukleotidové; antibakteriální látky; Anti-Bacterial Agents; imunoanalýza; laboratoř na čipu; Antibodies; Electrophoresis, Capillary; protilátky; elektroforéza kapilární; Aptamers, Nucleotide